Optical and MRI-Guided Theranostic Application of Ultrasmall Superparamagnetic Iron Oxide Nanodrug Conjugate for PSMA-Positive Prostate Cancer Therapy - Surasinghe, Sharmane; Liatsou, Ioanna; Nováková, Zora; Bařinka, Cyril; Artemov, Dmitri; Hapuarachchige, Sudath (ACS applied materials & interfaces, 2025)
Active targeting is more effective than conventional passive targeted drug delivery systems in increasing therapeutic efficacy and minimizing systemic toxicities. Importantly, the nanoparticle-based targeted drug delivery systems combine active and passive targeting properties and significantly enhance therapeutic efficacy. In this study, we utilized ultrasmall superparamagnetic iron oxide (uSPIO) nanoparticles conjugated with anti-prostate-specific membrane antigen (PSMA) 5D3 monoclonal antibody, mertansine (DM1) antitubulin agent, and fluorophore to develop a targeted uSPIO-5D3-DM1-AF488/CF750 nanotheranostic for PSMA(+) prostate cancer (PC) therapy. This agent enables multimodality in vivo imaging using near-infrared (NIR) fluorescence and magnetic resonance imaging (MRI). uSPIO-5D3-DM1-AF488 is selectively internalized into PSMA-positive cells by receptor-mediated endocytosis, and uSPIO-5D3-DM1-CF750 exhibited 1.62 and 166.2 ng/mL IC50 values in PSMA(+) and PSMA(-) cells, respectively. The image-guided therapeutic study was conducted in vivo in human PC xenograft mouse models bearing bilateral PSMA(±) tumors (n = 10, two 10 mg/kg doses on days 1 and 14). The therapeutic results exhibited a significant control of the growth of PSMA(+) tumors starting at day 5 (p = 0.05) and significantly improved efficacy after day 9 (p = 0.0005) during the treatment period (t = 21 days). We observed the PSMA-specific uptake of uSPIO-5D3-DM1-CF750 in tumors in NIR IVIS Xenogen images and T1- and T2-weighted MRI with 20.6% and 42% reduction of overall T1 and T2, respectively. Approximately 70% of mice with PSMA(+) tumors treated with uSPIO-5D3-DM1-CF750 survived or did not exceed the threshold level of the tumor size during the treatment. Ex vivo biodistribution study proved 50% and 45% higher uptake of uSPIO-5D3-DM1-CF750 by PSMA(+) tumors compared to untargeted uSPIO-DM1-CF750 by PSMA(+) tumors and uSPIO-5D3-DM1-CF750 by PSMA(-) tumors, respectively. ICP-MS analysis demonstrated a 73% increase in uSPIO-5D3-DM1-CF750 uptake by PSMA(+) tumors compared to PSMA(+) tumors treated with pure uSPIO. The toxicological results reveal the safe profile in systemic toxicities without life-threatening changes in the complete blood count and clinical chemistry profile of toxicology.
Keywords: antigeny povrchové; Animals; glutamátkarboxypeptidasa II; Magnetic Resonance Imaging; teranostická nanomedicína; Cell Line, Tumor; optical imaging; prostate cancer; image-guided drug delivery; Mice, Nude; ultrasmall superparamagnetic iron oxide nanoparticles; Antibodies, Monoclonal; lidé; Mice; magnetické nanočástice oxidů železa; Magnetic Iron Oxide Nanoparticles; magnetická rezonanční tomografie; targeted therapy; Magnetite Nanoparticles; Dextrans; nádory prostaty; dextrany; myši; Prostatic Neoplasms; Male; Theranostic Nanomedicine; maytansin; Glutamate Carboxypeptidase II; monoklonální protilátky; prostate-specific membrane antigen; MRI; mužské pohlaví; zvířata; Maytansine; Antigens, Surface; magnetické nanočástice; myši nahé; nádorové buněčné linie; anti-PSMA antibody; Humans